The role of religiosity, product knowledge and product assessment on digital purchasing of halal products - Darsita Suparno; Ahmad Satori Ismail; Nadra Nadra; Ita Fitriana (International Journal of Data and Network Science)
The study surveys the effects of religiosity and Knowledge of halal products on both product assessment and digital purchasing interest. The study also investigates the effects of religiosity and halal product assessment on digital product purchase interest. This research method is to use quantitative methods to test the relationship between dependent and independent variables. The population of this study is consumers of halal products and the sample of this study is 564 consumers of halal products determined by the simple random sampling method. The research analysis uses the structural equation modeling partial least squares (SEM-PLS) method and uses data processing tools with SmartP LS 4.0 software. The research questionnaire contains statement items using a 7-point Likert scale, namely (1) strongly disagree, (2) disagree, (3) somewhat disagree, (4) neutral, (5) somewhat agree, (6) agree and (7) strongly agree. The independent variables of this research are Religiosity, Knowledge of halal products, and Product assessment and the dependent variable is digital purchasing interest. The stages of research data analysis are the outer model test including reliability and validity tests and the inner model test including termination tests and hypothesis tests. Based on the results of research data analysis, it can be concluded as follows: Religiosity has a positive and significant effect on the assessment of halal products, meaning that the higher the religiosity obtained by customers, the higher the assessment of halal products. Knowledge of halal products has a positive and significant effect on the assessment of halal products, meaning that the higher the knowledge of halal products, the higher the assessment of halal products. Religiosity has a positive and significant effect on interest in buying halal products, meaning that the higher the religiosity obtained by customers, the interest in buying halal products will increase. Knowledge of halal products has a positive and significant effect on buying interest, meaning that the higher the customer's perceived knowledge of halal products, the more buying interest will increase. The assessment of halal products has a positive and significant effect on interest in buying halal products, meaning that the higher the understanding of the assessment of halal products, the higher the level of interest in buying halal products.